(3JMaI GdJOHjQ dCgd GdJHUjQs - (3ESeGYjd GdJhfSjs
(3ChdgG (B:s
(3gPg QSGdI ai Yde GdUfYI GdEdgjI JSei JMJhi Ydi CQHYI CYeGd CUhd hSHYI aUhd GdaUd GdChd ai Yed GdCQhGL s
(3BNQgG (B:s
(3hEjGc Ke EjGc JNQL ef XGgQ GdcdGe Edi HGWfg aEffi hGddg bO cTaJ GdUfYI hQaYJ MLGHgG hChVMJ QehRgG hgJcJ SJQgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeS YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B364s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
(3JHUQI GdJQGLe(Bs
(3JQLeI GdeDda (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs